Pengaruh Gaya Kepemimpinan Demokratis, Motivasi Kerja dan Pemberian Kompensasi terhadap Upaya Meningkatkan Loyalitas Kerja Pegawai Studi pada Dinas Pariwisata Daerah Istimewa Yogyakarta - Gesang Sutopo; Jajuk Herawati; Epsilandri Septyarini (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine the effect of democratic leadership style variables, work motivation and compensasion on the work loyalty of study employees at the special Region of Yogyakarta Tourism Office.The population used in this study amounted to 74 employees with the sampling technique. The method used in this study is a quantiative method with the help of IBM SPSS Statistic 22. Data collection techniques in this study used questionnaires distributed to respondents with a likert scale. The results of this study indicate that there is influence of democratic leadership style varables, work motivation and compensastion on employee loyalty of the Special Region of Yogyakarta Tourism Office. Homewer, only the democratic leadership style variable has been tested and has a positive and significant effect on employee loyalty. But work motivation and compensation do not have a partial effect on employee loyalty.